Street Networks and Urban Sustainability by Quantifying Connectivity, Accessibility, and Walkability for Resilient Cities - Al-Saaidy, Haider J. E.; Alobaydi, Dhirgham; Abdullah, Sally F. K. (Salehan Institute of Higher Education, 2025)
Street networks are crucial in shaping the quality of urban life. Through their impact on mobility and social interaction, they play a critical role in shaping how people move around the city and determine the connectivity, accessibility, safety, and convenience of different areas. Thus, it is essential to develop a systematic understanding of street networks to create livable, sustainable, accessible, and equitable cities. The aim of this study is to analyze and develop the role of street networks in shaping urban mobility, connectivity, and accessibility, and thereby enhance sustainable urban living by creating people-centric cities. Quantitative techniques and measures are employed to examine urban structure metrics to understand both physical and spatial characteristics at micro and macro scales. Three primary parameters for the configuration of street patterns - grid pattern ratio (GPR), pedestrian route directness factor (PRD/PRF), and ped-shed (PS) and effective walking area (EWA) - are selected to compute the formational attributes of selected streets in Baghdad, Iraq. The evaluation employs different arithmetic methods linked with a Geographical Information System (GIS) to quantify and compare two examined areas, and the results reveal a contradiction in the spatial configuration of the sample street patterns. From these findings, the paper offers specific recommendations and urban design guidelines to improve the quality of similar urban areas. The paper concludes that in-depth knowledge of a street’s role in its urban context helps to optimize spatial configuration processes in the built environment.